Three new species of Spiladarcha Meyrick, 1913 (Lepidoptera: Urodidae) from Costa Rica - Sohn, Jae-Cheon (Zootaxa, 2014)
Three new species of Spiladarcha are described from Costa Rica, including S. puravida n. sp., S. septifera n. sp., and S. tuberculata n. sp. The genus Spiladarcha is reported from Costa Rica for the first time. Synapomorphies of Spiladarcha are revised. Photos of adult habitus and genitalia of known sexes are provided.